2018
DOI: 10.1002/etc.4115
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of interspecies interaction, temperature, and zinc on Daphnia longispina population dynamics

Abstract: Under natural conditions, organisms can experience a variety of abiotic (e.g., temperature, pH) and biotic (e.g., species interactions) factors, which can interact with toxicant effects. By ignoring species interactions conventional ecotoxicological studies (i.e., single-species tests) oversimplify the actual field situation. We investigated whether temperature and interspecific competition affected the effects of zinc (Zn) on a Daphnia longispina population. The D. longispina populations were exposed in a ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…However, Daphnia might be sensitive to some compounds. For this reason they are sometimes used to test water quality (Heger et al, 2018;Van de Perre et al, 2018) because many compounds are toxic for these organisms (Sladkova et al, 2016). Nitrate (NO3 -) concentrations above 56 mgN-NO3 -L -1 (250 mgNO3 -L -1 ) together with a water temperature of 26 °C proved to have lethal effects on a Daphnia population (Maceda-Veiga et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, Daphnia might be sensitive to some compounds. For this reason they are sometimes used to test water quality (Heger et al, 2018;Van de Perre et al, 2018) because many compounds are toxic for these organisms (Sladkova et al, 2016). Nitrate (NO3 -) concentrations above 56 mgN-NO3 -L -1 (250 mgNO3 -L -1 ) together with a water temperature of 26 °C proved to have lethal effects on a Daphnia population (Maceda-Veiga et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, although somewhat more speculative, species interactions (absent in single‐species studies) may have affected the toxicity‐modifying effect of pH on Pb toxicity. Van De Perre et al 2018, for instance, demonstrated that the addition of a rotifer ( Brachionus ) to a test system affected the toxicity‐modifying effect of temperature on Zn toxicity to a Daphnia population. However, we are unaware of similar types of studies with phytoplankton communities.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the effect of metals at the population level, one can perform population‐level experiments such as mesocosms or microcosms (Van de Perre et al 2018; Pereira et al 2019). However, this is not always feasible due to ethical and practical constraints, especially for vertebrate organisms such as fish.…”
Section: Introductionmentioning
confidence: 99%